AB0311 The 158vv fcgamma receptor iiia genotype predicts a positive response to rituximab in rheumatoid arthritis: Analysis in a large cohort of italian patients. (23rd January 2014) - Fabris, M.; Quartuccio, L.; Pontarini, E.; Zabotti, A.; Benucci, M.; Manfredi, M.; Biasi, D.; Ravagnani, V.; Atzeni, F.; Morassi, P.; Fischetti, F.; Bazzicchi, L.; et al.
Abstract : Background: Receptors for IgG play an important part in immune complex clearance. Several studies have investigated the polymorphism 158V/F of Fc fragment of IgG (FcgR) type IIIa as genetic factor influencing disease course after rituximab (RTX) therapy in several rheumatologic and haematological diseases, with contrasting, unreplicated results. Objectives: To investigate the FcgRIIIa 158V/F polymorphism in a large Italian retrospective cohort of patients with rheumatoid arthritis treated with RTX. Methods: The study was conducted in 222 unselected RA patients referred to 13 rheumatologic centres in Italy. All patients were treated with RTX (alone or in combination with DMARDs) at standard doses. Response to therapy (DAS28; EULAR criteria) was evaluated at months +4 (data available in 213 cases) and +6 (data available in all cases) after the first RTX infusion. The FcgRIIIa polymorphism was analysed by PCR followed by Sanger's sequencing. Results: Patients with the VV genotype showed the highest rate of response to RTX both at month +4 (good/moderate in 32/37, 86.5% of the VV patients) and at month +6 (good/moderate response in 34/38, 89.5% of the VV patients) while VF and FF patients showed the same response rate either at month +4 (good/moderate in 70/103, 68% VF and in 53/73, 72.6% FF patients; VV versus VF/FF: OR 2.76, 95%CI 1.02-7.47, *p=0.043) and at month +6 (good/moderate in 69/105, 65.7% VF and in 49/75, 65.3% FF patients; VV versus VF/FF: OR 4.47, 95%CI 1.52-13.16, **p=0.0032). Conclusions: The VV genotype of the 158V/F FcgRIIIa polymorphism identifies RA patients who demonstrate the highest rate of positive response to RTX. By contrast, no difference was noticed between VF and FF patients. Disclosure of Interest: None Declared